GROWTH AND YIELD ENHANCEMENT OF MUNGBEAN (VIGNA RADIATA L.) BY SOURCES AND LEVELS OF PHOSPHORUS AND PHOSPHATE SOLUBILIZING MICROBES - SINGH, BHARAT; SINGH, C.P.; PARIHAR, S.S. (Annals of Agricultural Research, 2014)
A field experiment was conducted to study the effect of different sources and levels of phosphorus, with and without PSM on growth and yield of mungbean (grain and stover). Application of P along with PSM (growth and yield) showed additive effect on these parameters. Under all Phosphorus x PSM treatments the growth and yield were higher with 60 kg P2 O5 ha-1 than with the lower & higher levels of P. The effect of different sources of phosophorus with PSM on mungbean growth and yield was in order of : RP > DCP > SSP with PSM. The highest yield of grain (8.81 q ha-1) and stover yield (8.63 q ha-1) was obtained with inoculation.